Performance analysis of self-compacting concrete with use of artificial aggregate and partial replacement of cement by fly ash - Patil, Abhay; Jayale, Vivek; Prakash Arunachalam, Krishna.; Ansari, Khalid; Avudaiappan, Siva; Agrawal, Dhiraj; Kuthe, Abhaykumar M.; Alharbi, Yousef R.; Amir Khan, Mohammad.; Roco Videla, Ángel Gerardo. (MDPI, 2024)
Artificial aggregate (AF), i.e., silico manganese (SiMn) slag aggregate, is a byproduct of ferromanganese and silico manganese alloy production. The utilization of industrial waste and industrial byproducts in construction has increased the aim of conserving natural resources to nurture a pollution-free environment. The current study examines the performance of the use of artificial aggregate (AF) and partial replacement of cement with fly ash (FA). The properties of fresh concrete, as well as the compressive and flexural strength and split tensile strength of concrete were evaluated. Seven mix proportions were prepared for M30-grade concrete. The first was a control mix (with 0% AF and FA), three other mixes contained varying amounts of AF (20%, 40%, and 60%) as a partial replacement of CA with AF. The average compressive strength of the control SCC was found to be 32.87 MPa (megapascals) at the age of 28 days, and after replacing 20% natural aggregate with artificial aggregate, the compressive strength increased by 8.27%, whereas for 40% and 60% replacement, it decreased by 4.46% and 12.55%, respectively. Further investigation was performed on the optimum value obtained by replacing 20% of CA with AF. At this percentage, cement was replaced by FA at (15%, 25%, and 35%) where at 15%, the average compressive strength increased by 7.41%, whereas for 25% and 35% replacement, it decreased by 7.47% and 17.19%, respectively. For SCAF20 and SCF15, all strengths were at maximum due to the increase in its density. The findings show that the development of advanced construction materials is environmentally sustainable.
Keywords: Artificial aggregate; Self-compacting concrete; Superplasticizer; Viscosity modifying agent; Cenizas volantes